1997
DOI: 10.1177/030913339702100402
|View full text |Cite
|
Sign up to set email alerts
|

Floodplain biogeomorphology

Abstract: Floodplains are unique ecosystems because of their linear form, the sometimes extreme dynamism of their geomorphology and because they process large fluxes of energy and materials from upstream areas. This article focuses on the importance of hydrological inputs to floodplains through 1) their influence on the arrangement of landforms and vegetation communities and 2) the connections between flooding regimes and the regeneration and turnover time of floodplain vegetation. Many researchers have demonstrated clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
193
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(201 citation statements)
references
References 111 publications
4
193
1
3
Order By: Relevance
“…It is well established that on many floodplains, regeneration is periodic and related to provision of very particular conditions of water availability and disturbance patterns during the first year of growth following germination. Thus, willows require open, well-watered but not waterlogged sites for successful regeneration; the seedlings must then not be subjected to physical disturbance by flooding or ice until they are well established (Johnson et al 1976;Bradley and Smith 1986;Mahoney and Rood 1991;Hughes 1997). …”
Section: Regeneration Niches and Sssmentioning
confidence: 99%
“…It is well established that on many floodplains, regeneration is periodic and related to provision of very particular conditions of water availability and disturbance patterns during the first year of growth following germination. Thus, willows require open, well-watered but not waterlogged sites for successful regeneration; the seedlings must then not be subjected to physical disturbance by flooding or ice until they are well established (Johnson et al 1976;Bradley and Smith 1986;Mahoney and Rood 1991;Hughes 1997). …”
Section: Regeneration Niches and Sssmentioning
confidence: 99%
“…Besides providing natural habitat for various river ecosystem species (Hughes, 1997), riparian trees interact with river streamflow thus contributing to a number of fundamental feedback dynamics. Examples are the lateral and longitudinal connectivity between the river and the floodplain, the control of water quality by biological filtering, the influence on sedimentary processes (Edwards et al, 1999;Schnauder and Moggridge, 2009) and the spatial spreading of species (Johnson, 2000;Mahoney and Rood, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, erosion of vegetated non-cohesive alluvial sediment such that forming river bars and islands has only recently been attracting the interest of scientific communities with regard to river restoration projects (e.g. Palmer et al, 2007) and the related implications for the connected riparian ecosystem (Decamps et al, 1988;Hughes, 1997;Tockner and Stanford, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Water flow is a major structural factor in ecological communities and is an important driving force of com-munity composition in riparian habitats, because of the temporal and spatial variability of flood and drought (Walker et al 1995;Hughes 1997;Poff et al 1997;Richter et al 1997;Ward 1998;Nilsson and Svedmark 2002). A number of eco-hydrological studies have identified relationships between riparian vegetation and hydrologic parameters, including frequency, timing, duration, rate of change, and magnitude of base flows (Nilsson and Svedmark 2002;Elmore et al 2003).…”
Section: Introductionmentioning
confidence: 99%